An Alternative Approach to the Surface Methacrylation of Non-stoichiometric Hydroxyapatite Nanoparticles for Use in Bone-Inspired Composites - Comeau, Patricia A.; Willett, Thomas (Frontiers in Materials, 2019)
Modification of the inorganic particle surface is one approach towards enhancing the mechanical and swelling properties of a bone-inspired composite. While silanization of nHA (Si-nHA) is a recognized functionalization approach, one notable disadvantage is the need for relatively harsh reaction conditions. In this study, we sought to functionalize the surface of non-stoichiometric nHA particles by utilizing a gentler methacrylation approach with two different methacrylates – methacrylic anhydride (MAh) and glycidyl methacrylate (GMA). ATR-FTIR and liquid state 13C-NMR provided evidence for a stronger affinity of the nHA surface for methacrylic anhydride compared to glycidyl methacrylate under the same reaction conditions; fewer GMA molecules attached to the nHA surface. However, the affinity of MAh is more electrostatic in nature, whereas GMA attachment involves covalent bond formation. In addition, while in water, there was no detectable dependence of particle settling on methacrylate choice, in ethanol, native nHA and nHA methacrylated with GMA each had detectably greater stability in suspension than the other sample groups. Lastly, the addition of GMA-nHA detectably increased the dynamic stiffness and did not impact the swelling in 37 °C water of a GelMA-based composite compared to that observed upon adding native nHA. Overall, the GMA-based methacrylation approach was found to be a viable alternative to silanization and offers possibilities for future fabrication of bone-inspired composites.